2006
DOI: 10.1088/0957-0233/17/5/s16
|View full text |Cite
|
Sign up to set email alerts
|

Quantum dots as self-referenced optical fibre temperature probes for luminescent chemical sensors

Abstract: The use of semiconductor nano-particles as temperature probes in luminescence chemical sensing applications is addressed. Temperature changes the intensity, the peak wavelength and the spectral width of the quantum dots luminescent emission in a linear and reversible way. Results are presented that show the feasibility of implementing a self-referenced intensity-based sensor to perform temperature measurements independent of the optical power level in the sensing system. A resolution of 0.3 • C was achieved. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 25 publications
1
44
0
Order By: Relevance
“…8 In addition, recent works have demonstrated the ability of QDs to act as nano-thermometers based on the thermal sensitivity of their fluorescence bands. [9][10][11][12][13][14] Based on all these outstanding properties, QDs have been successfully used to mark specific receptors in cell membranes, to measure intracellular temperature, and to label living embryos at different stages. 9,[15][16][17] Most of the QD-based bio-images reported up to now were obtained by using either CdSe or CdTe QDs, since both are currently commercially available with a high degree of quality.…”
Section: Introductionmentioning
confidence: 99%
“…8 In addition, recent works have demonstrated the ability of QDs to act as nano-thermometers based on the thermal sensitivity of their fluorescence bands. [9][10][11][12][13][14] Based on all these outstanding properties, QDs have been successfully used to mark specific receptors in cell membranes, to measure intracellular temperature, and to label living embryos at different stages. 9,[15][16][17] Most of the QD-based bio-images reported up to now were obtained by using either CdSe or CdTe QDs, since both are currently commercially available with a high degree of quality.…”
Section: Introductionmentioning
confidence: 99%
“…These data can be approximated by an exponential signal with a correlation factor of R 2 = 0.998, rather better than the obtained absorption spectra measured in the precedent section. In some previous works [26][27][28]30], the sensors apparently showed a linear behavior due to the narrower temperature range used. The average sensitivity of this sensor is 0.00465…”
Section: Emission Studymentioning
confidence: 84%
“…The emission intensity decreases, and the emission bands move to higher wavelengths when temperature increases. Due to these features, QDs are an excellent material for temperature sensing [25][26][27][28].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These semiconductor nanoparticles offer several advantages including narrow fluorescence emission, tunable wavelength, relatively high quantum yield, outstanding photo stability as well as flexible photo excitation. It also has been reported that the behavior of the luminescent properties of quantum dots with temperature has suitable characteristics for application as temperature probes [10][11][12][13][14][15]. The luminescence properties, such as the excited state lifetime, emission intensity, and peak wavelength, have been proven to be good indicators of temperature.…”
Section: Introductionmentioning
confidence: 99%